2021
DOI: 10.1186/s12879-021-06287-1
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic prescriptions and risk factors for antimicrobial resistance in patients hospitalized with urinary tract infection: a matched case-control study using the French health insurance database (SNDS)

Abstract: Background Antibiotic resistance is increasing among urinary pathogens, resulting in worse clinical and economic outcomes. We analysed factors associated with antibiotic-resistant bacteria (ARB) in patients hospitalized for urinary tract infection, using the comprehensive French national claims database. Methods Hospitalized urinary tract infections were identified from 2015 to 2017. Cases (due to ARB) were matched to controls (without ARB) accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This observation is consistent with pre-COVID-19 findings suggesting that ICU patients, and particularly those for whom invasive interventions are used, are at increased risk of hospital-acquired infections. 169 , 170 In our analysis, antibiotic exposure was a significant risk factor for antimicrobial resistance, consistent with mechanisms described in the literature. 171 , 172 IL-6 inhibitor use and diabetes were also associated with higher proportions of antimicrobial resistance at the patient level.…”
Section: Discussionsupporting
confidence: 87%
“…This observation is consistent with pre-COVID-19 findings suggesting that ICU patients, and particularly those for whom invasive interventions are used, are at increased risk of hospital-acquired infections. 169 , 170 In our analysis, antibiotic exposure was a significant risk factor for antimicrobial resistance, consistent with mechanisms described in the literature. 171 , 172 IL-6 inhibitor use and diabetes were also associated with higher proportions of antimicrobial resistance at the patient level.…”
Section: Discussionsupporting
confidence: 87%
“…There was an increasing trend in antimicrobial resistance associated with more RUTI episodes [ 32 ]. Genomic surveillance of antibiotic-resistant uropathogens shows that drug-resistant clones persisted within and transmitted between the intestinal and urinary tracts of patients affected by RUTI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in hospitals has consistently identified positive associations between antibiotic use and infection or colonization with MDR bacteria [8] , [9] , [10] . Additional correlates of MDR infection or colonization within clinical settings include measures of health care exposure such as invasive procedures, use of catheters or intubation [11] , [12] , [13] , previous hospitalization [14] , [15] , [16] , and length of hospital stay [ 9 , 17 ]. However, more studies have examined the risk factors associated with infection without considering colonization with MDR organisms as an end point of interest, and most of these studies have been carried out in high-income settings.…”
Section: Introductionmentioning
confidence: 99%